(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the prospects for the development of Islamic finance in Uzbekistan. The Republic of Uzbekistan has made great strides since independence, including freedom of religion and conscience, national legislation and the development of the national economy.